2007
DOI: 10.1111/j.1463-1326.2007.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D in the pathogenesis of type 2 diabetes mellitus

Abstract: Vitamin D deficiency has been shown to alter insulin synthesis and secretion in both humans and animal models. It has been reported that vitamin D deficiency may predispose to glucose intolerance, altered insulin secretion and type 2 diabetes mellitus. Vitamin D replenishment improves glycaemia and insulin secretion in patients with type 2 diabetes with established hypovitaminosis D, thereby suggesting a role for vitamin D in the pathogenesis of type 2 diabetes mellitus. The presence of vitamin D receptors (VD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
328
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(342 citation statements)
references
References 106 publications
6
328
1
7
Order By: Relevance
“…Vitamin D is stored in inactive form in liver and adipose tissue. The activation of Vitamin D (hydroxylation reaction) occurs in liver and kidneys and finally gets activated to calcitriol (1,25 DHCC) [22]. In healthy subjects, Vitamin D deficiency occurs mainly because of low dietary intake and less exposure to sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is stored in inactive form in liver and adipose tissue. The activation of Vitamin D (hydroxylation reaction) occurs in liver and kidneys and finally gets activated to calcitriol (1,25 DHCC) [22]. In healthy subjects, Vitamin D deficiency occurs mainly because of low dietary intake and less exposure to sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Data from various epidemiological studies have suggested that there is link between vitamin D3 and development of type 1 diabetes [12,13]. Literature also reports the vitamin D receptor gene polymorphism in relation with type 1 diabetes [14,15]. Studies reveal the association between vitamin D and β cell function, insulin secretion and its action.…”
Section: Diabetes and Vitamin Dmentioning
confidence: 99%
“…Here we are limited to small interventions and animal studies. In type 2 diabetes very high doses of 25-(OH)D have been administered, but the data are confusing, whereas in type 1 diabetes 1,25-(OH)2D has mainly been given, with little or no effect on C-peptide preservation in newly diagnosed type 1 patients [7,8]. What about NOD mice?…”
Section: Cyp27b1mentioning
confidence: 99%